Pelatihan Tata Cara Membatik Tema Ekosistem Mangrove bagi Pengelola Wisata Alam Cisiu: Training on Mangrove Ecosystem Theme Batik for Natural Tourism Managers - Fuad, Mochamad Arif Zainul; Harlyan, Ledhyane Ika; Purwanti, Pudji; Hidayati, Nurin; Rahmawati, Andira; Masdian, Nuril Haq Bilqishima; Prasetio, Rachmat Ramadhan; Putra, Valeryan Ramana; Rahmanissa, Aulia Intan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The sustainable management of mangrove ecotourism requires generating additional income for its managers. One potential strategy is batik training using mangrove ecosystem motifs. On September 15, 2024, a batik training session was conducted for tour guides and managers of the Mangrove Cisiu Eco-Education Park, located in Pangkah Kulon Village, Gresik. The event was attended by 10 participants and was part of the Community Partnership Program (PKM) titled